The conceptual framework of the bioethical issues: an indicative commentary - Χωριανοπούλου (Maria Chorianopoulou), Μαρία (Bioethica, 2018)
The aim of this study is to briefly examine and critically evaluate certain philosophical approaches of the utmost importance on the concepts of human dignity and autonomy. Since these notions are systematically invoked in the context of the current bioethical debates, it is imperative that their exact content be clarified. Thus, aspects of the human dignity are traced back to the stoic, Christian, Kantian, and post-Kantian tradition, while on the other hand two major conceptions of autonomy are analysed (autonomy conceived as self-determination and as self-restriction) along with their respective bioethical implications. Human dignity and autonomy being related to extremely divergent meanings, it follows that conceptual clarity is an indispensable prerequisite for conducting fruitful bioethical discussions